PERKEMBANGAN DAN PEMILIHAN PRIORITAS JENIS INDUSTRI HILIR TEH INDONESIA - SUPRIHATINI, ROHAYATI (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 4, No. 3 November2004, 2012)
The pusposes of this study are to understand development of tea down-stream industries in Indonesia and to select the priority of those industries type to be developed. Comparative Performa Index (CPI) analysis and Eickenrode weighting method was applied. The results showed that the development of tea down-stream industries in Indonesia in the 1998-2001 period tend to increase. The typical of tea down-stream industries that could be prioritized consecutively for their development were as followed: (1) extract tea, (2)packing and bulk black tea, and (3) ready to drink with tea aroma. Those mentioned industries, therefore, should get good facilities and services from the government in dealing with licensing, funding and taxation.
Keywords: Indonesia, Development, Priority, Tea, Dwn-Sream, Idustry